2021
DOI: 10.1007/s00540-021-02972-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevoflurane exposure during different stages of pregnancy on the brain development of rat offspring

Abstract: Objective This study explored the effects of sevoflurane exposure during different stages of pregnancy on the brain development of offspring. Methods Thirty-six pregnant SD rats were randomly divided into 4 groups: control, sevoflurane exposure in early (S1) pregnancy, sevoflurane exposure in middle (S2) pregnancy, and sevoflurane exposure in late (S3) pregnancy. After natural birth, the learning and memory capacity of offspring rats was analyzed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Disruption of angiogenesis during intrauterine development may lead to intrauterine growth retardation and various related pathologies (20). While many studies have examined the effects of sevoflurane exposure at different stages of pregnancy, research on its impact on placental angiogenesis remains scarce (21,22). A multicenter cohort study investigating long-term fetal exposure to volatile anesthetic agents assessed 15,317 children born to 9,433 nursing mothers exposed to anesthetic gases during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of angiogenesis during intrauterine development may lead to intrauterine growth retardation and various related pathologies (20). While many studies have examined the effects of sevoflurane exposure at different stages of pregnancy, research on its impact on placental angiogenesis remains scarce (21,22). A multicenter cohort study investigating long-term fetal exposure to volatile anesthetic agents assessed 15,317 children born to 9,433 nursing mothers exposed to anesthetic gases during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthetics have also been associated with neurobehavioral abnormalities following prenatal exposure (reviewed in Andropoulos 2018 ), particularly if the exposure occurs early in pregnancy ( Cui et al, 2021 ). In a transgenerational mouse study modeling human anesthesia, gestational exposure to sevoflurane led to anxiety and impairments in social interaction in the following three generations through the paternal lineage ( Wang et al, 2021 ).…”
Section: Multigenerational Risk For Asdmentioning
confidence: 99%
“…Despite the widespread use of Sv, certain studies have reported cases of neurotoxicity due to increases in neuroinflammation and oxidative stress, decreases in neuronal transmission, changes in lipid membrane fluidity and apoptosis of neuroprogenitor cells, which suggests that exposure may confer long-term adverse consequences (6)(7)(8). A number of reports have indicated that exposure to Sv, particularly during the early and mid-pregnancy periods, can also reduce postnatal learning and memory capacity (9,10). The exposure time and dose are considered the most important determinants of the activation of damage pathways by this anesthetic.…”
Section: Introductionmentioning
confidence: 99%